Governance of 3-D Printing Applications in Health: Between Regulated and Unregulated Innovation - Tesh W. Dagne (Science and Technology Law Review, 2020)
The article aims to examine how governance frameworks under regulatory and liability rules in the United States and Canada respond to the challenges and opportunities presented by three-dimensional printing (3DP) applications in health. The discussion demonstrates that 3DP applications in health currently fall between regulated and unregulated innovation, given that existing governance frameworks do not sufficiently capture 3DP’s unique attributes and potential. In identifying approaches to regulatory intervention in the governance of 3DP innovation, the discussion outlines characteristics of 3DP that lend themselves to a model of innovation governance that would allow pre-emptive regulatory actions for optimal outcomes. Thus, the article advances the position that the state of the technology’s development in health applications has matured to such a level that a dedicated regulatory framework is necessary for addressing the uncertainty of risks and for promoting an understanding of the applicability of existing regulatory requirements to guide the flourishing innovation.